2009
DOI: 10.1088/1748-9326/4/2/025001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal rainfall fluctuations in Israel and their possible link to urban and air pollution effects

Abstract: In this paper we analyze spatial variations of the annual rainfall that have taken place in the non-arid regions of Israel (annual rainfall > 200 mm) during the years 1952-2006, incorporating all available data. The results of the present study over the research area as a whole indicate that no significant temporal change of the annual rainfall occurred in any region of the study area. However, focusing on spatial rainfall fluctuations between sub-regions in the study area, a significant increase was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…In general, results from the metropolitan meteorological experiment have shown that during the summer months, urban effects lead to increased precipitation at distance of 30e75 km away from the city center. This finding has been confirmed in many previous studies (Landsberg, 1970;Sanderson and Gorski, 1978;Bornstein and Lin, 2000;Shepherd et al, 2002;Shepherd, 2005;Shepherd, 2006;Mote et al, 2007;Hand and Shepherd, 2009;Halfon et al, 2009). However, using satellite data that reveals plumes of reduced cloud particle size and suppressed precipitation, Rosenfeld (2000) demonstrated that urban and industrial air pollution can prevent precipitation in urban areas.…”
Section: Introductionsupporting
confidence: 74%
“…In general, results from the metropolitan meteorological experiment have shown that during the summer months, urban effects lead to increased precipitation at distance of 30e75 km away from the city center. This finding has been confirmed in many previous studies (Landsberg, 1970;Sanderson and Gorski, 1978;Bornstein and Lin, 2000;Shepherd et al, 2002;Shepherd, 2005;Shepherd, 2006;Mote et al, 2007;Hand and Shepherd, 2009;Halfon et al, 2009). However, using satellite data that reveals plumes of reduced cloud particle size and suppressed precipitation, Rosenfeld (2000) demonstrated that urban and industrial air pollution can prevent precipitation in urban areas.…”
Section: Introductionsupporting
confidence: 74%
“…The observed decreasing trend in rain frequency along Hengduan Mountain reflects the impacts of enhanced aerosols on the orographic precipitation (Givati and Rosenfeld, 2004;Rosenfeld et al, 2007). In the upwind region, the decreasing trend of rain frequency coincided well with the increasing trend in coarse mode AOD (Alpert et al, 2008;Halfon et al, 2009;van den Heever and Cotton, 2007). Also as shown in Fig.…”
Section: Resultssupporting
confidence: 59%
“…Human-induced climate change has caused a redistribution of precipitation (Alpert et al, 2008;Changnon et al, 1981;Halfon et al, 2009;Lowry, 1998;van den Heever and Cotton, 2007;. Besides the greenhouse gasesCorrespondence to: Q.…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnitude and even sign of the effect that decreased droplet sizes has on precipitation is less clear (Stephens and Feingold, 2009;Levin and Cotton, 2008). Some conclude that the aerosol influence on precipitation is small or even negligible (e.g., Alpert et al, 2008;Halfon et al, 2009;Schultz et al, 2007). Others find an effect (e.g.…”
Section: Introductionmentioning
confidence: 99%